Adaptive Reuse Bangunan Rumah Sakit Dharma - Muhammad Zemmy Alfikri (MES Bogor, 2024)
This research focuses on adapting (adaptive reuse) the Dharma Hospital building into a fitness center and cafe using quantitative methods. The aim of this research is to evaluate and understand how existing hospital buildings can be transformed and reused in attractive and profitable ways. Quantitative methods are used to collect and analyze data about the physical condition of buildings, space requirements, and user preferences. The research results show that with a creative approach, hospital buildings can be adapted to become modern and comfortable fitness centers and cafes while maintaining their historical and architectural value. The conclusion of this research is that adaptive reuse is an innovative and potential strategy for reusing hospital buildings that are no longer in use. This can not only improve people's quality of life and health, but can also provide added economic and social value.